Factors influencing decision-making of rice farmers towards productivity among Integrated Agricultural Development Areas (IADA) in Malaysia - Mohamed Haris, Nur Bahiah; Hamzah, Azimi; Krauss, Steven Eric; Ismail, Ismi Arif (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
The Malaysian rice industry is carefully monitored by several relevant agencies as it is a major priority in relation to the nation’s food security agenda. Against this backdrop, the current study focused on factors governing Malaysian rice farmers’ decision-making that contributes to their readiness to employ appropriate crop husbandry practices, which are critical for increasing productivity. Structured questionnaires were administrated to 320 respondents from six (6) Integrated Agricultural Development Areas (IADA) in Malaysia. Demographically, a majority of the respondents were aging farmers and were more interested in participating in hands-on extension clinics, rather than attending structured training sessions. The results further revealed the need for the younger generation to get involved in this area, to replace the aging farmers and to revitalize the sector toward becoming more successful in the years to come. Moreover, regression analysis also demonstrated four additional factors promoting higher paddy productivity: farming knowledge, motivational values, farming experience and trust in extension agents’ capabilities. From this combination of five factors, the current study has shed light on how Malaysian paddy farmers make decisions, which can be used to improve productivity within the IADAs. The study forwards potential approaches to making rice farming more attractive to the youth as a critical ingredient for the future health of the paddy industry.